Testing the relationship between financial sector output, employment and economic growth in North Cyprus - Behiye Cavusoglu; Saifullahi Sani Ibrahim; Huseyin Ozdeser (Financial Innovation, 2019)
Sound and efficient functioning of financial systems is critical to the economic prosperity of any economy. This paper investigates the tripartite relationship between financial sector output, employment and economic growth in North Cyprus. Using relevant time series data analysis (within the framework of structural breaks and VECM), we found that financial sector output in North Cyprus is sensitive to both internal and external shocks in that its economy is well linked with the global economy, in spite of the political isolation sustained since the bifurcation of Cyprus into North and South. The study further documents evidence of the neutrality hypothesis in the finance-growth nexus. The underlying variables were weakly connected in the short-run. However, economic growth responded to the short-run shocks and handled the equilibrating process of reverting to the long-run trend and thus, the demand following hypothesis is confirmed in the long-run.
Keywords: E44; G2; O11; 650; Financial sector output; Economic growth; Employment; Structural breaks